Dinamika Ratifikasi Konvensi Jenewa di Indonesia (The Dynamics of The Ratification of Geneva Convention In Indonesia) - Damareka, Muhammad Darrell; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
This study examines the dynamics of Indonesia’s ratification of the Geneva Conventions in relation to the development of human rights (HAM). Since the national movement era, the spirit of human rights recognition had emerged, later reinforced through Indonesia's ratification of the 1949 Geneva Conventions and the Additional Protocols in 1958. However, implementation at the national level has encountered obstacles, including slow legal harmonization and limited understanding of humanitarian law principles among state actors. The study employs a normative juridical method through a literature-based approach, focusing on developments from pre-independence to the reform era. Findings reveal that Indonesia’s cautious stance toward international obligations, institutional disagreements, and political dynamics have significantly influenced both the ratification process and its execution. The research recommends strengthening national legal frameworks and enhancing institutional capacity through training to ensure effective implementation of the Geneva Conventions' principle